Immunosuppressive therapy in patients with aplastic anemia: a single-center retrospective study. - Hasan Jalaeikhoo; Ahmad Khajeh-Mehrizi (PLoS ONE, 2015)
Aplastic anemia (AA) is a rare disease in which hematopoietic stem cells are severely diminished resulting in hypocellular bone marrow and pancytopenia. Etiology of AA includes auto immunity, toxins, infection, ionizing radiation, drugs and rare genetic disorders, but in the majority of cases no cause can be identified. In the present study we assessed response rate, survival, relapse and clonal evolution in patients with AA treated with immunosuppressive therapy.Patients with AA who received immunosuppressive therapy between May 1998 and September 2013 were included in this study. Patients with non-severe AA (NSAA) were treated with cyclosporine (CsA) and danazol while patients with severe AA (SAA) as well as patients with NSAA who progressed to SAA after beginning of the treatment, were candidates for receiving antithymocyte globulin in addition to CsA and danazol.Among the 63 studied patients, 29 (46%) had NSAA and 34 (54%) had SAA. Three months after treatment, overall response was 58.6% in NSAA and 12.9% in patients with SAA. Survival of all patients at 5, 10 and 15 years were 73%, 55% and 49%, respectively. Survival rates were significantly higher in patients with NSAA compared to patients with SAA as well as in patients who responded at 6 months compared to non-responders. The relapse risk was 39.7% at 10 years. Relapse occurred in patients who discontinued the therapy more than those who continued taking CsA (p value<0.01). The risk of clonal evolution was 9.9% at 10 years and 22.8% at 15 years after treatment.This long-term retrospective study indicated that immunosuppressive therapy should be recommended to patients with AA. Also, our experience indicated that immunosuppressive therapy should not be discontinued after response to therapy in patients with both NSAA and SAA due to high risk of relapse. Low dose of CsA should be continued indefinitely.